Boiler feed pump low load – leak off recirculation study - van Tonder, Daniël (Department of Mechanical Engineering, 2021)
For power plants that make use of high energy boiler feed pumps, there is a risk that the boiler feed pump may experience cavitation and overheating at low load and start-up conditions. These plants make use of a leak off or recirculation system that diverts some of the flow back to the feed water tank, ensuring that a minimum flow through the pump is maintained at low load and start-up operating conditions. The recirculation valve, also known as a leak off valve, experiences a very high pressure difference and cavitation pitting is common due to the water being close to saturation. There are various ways in which the recirculation flow is controlled in the industry such as open orifice, on/off binary type control valves, automatic recirculation valves (ARC) or modern modulating leak off systems. The valves themselves can also be simple plug type or make use of pressure staging to reduce the risk of cavitation. This project involves modelling the flow system around the boiler feed pump and its control for the various architectures employed in Eskom. This is to assist in understanding the reasons for cavitation damage that is found in some recirculation valves as well as the low load capability of the system. Single stage components with extremely high pressure drops are singled out as components with the highest risk of cavitation in the systems. Although extremely high pressure drops are found across the leak off valves themselves, the majority of the valves are multistage valves which are specifically designed to accommodate cavitation development and are therefore not of major concern. Some of the findings of the study are: The rule of thumb used within Eskom to determine the amount of pressure reducing stages on leak off valves could be more conservative. The specification of new valves and components for the leak off systems requires accurate specification based on detailed process models, such as the ones developed for this study. The full range of all possible operational cases must also be considered during the design.